Sustaining escapes from ultra-poverty: A mixed methods assessment of layered interventions in coastal Bangladesh - Diwakar, Vidya; Kamninga, Tony; Mehzabin, Tasfia; Tumusiime, Emmanuel; Kamal, Rohini; Pabony, Nuha Anoor (Chronic Poverty Advisory Network, 2024)
Bangladesh’s impoverishment is driven by climate-change shocks, healthcare expenses, poor access to agricultural markets, and the COVID-19 pandemic. Ultra Poor Graduation (UPG) programme, combined with inclusive Market Systems Development (iMSD), Disaster Risk Reduction (DRR), and Water, Sanitation, and Hygiene (WASH) interventions in south-west Bangladesh found that participation in the UPG programme with iMSD is associated with developing absorptive and adaptive resilience capacities to tackle chronic poverty. However, the study suggests that Disaster Risk Management (DRM) training, mobilization, and access to WASH services improve resilience capacities, preventing households from falling back into ultra-poverty.